2014
DOI: 10.2514/1.t4434
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Modeling of Pyrolysis Gas Transport Inside Charring Ablative Materials

Abstract: The behavior of pyrolysis gas transport in arcjet test samples is numerically studied. The simulation of the pyrolysis gas flow inside a porous material is presented, using two different geometries. The effects of allowing the gas to flow out of the sidewall are especially highlighted. Results show that the flow inside the test article is complex, and that the zero-dimensional or one-dimensional assumption made in most material response codes are not necessarily valid for certain geometries. The importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Recently, Weng and Martin [4] and Weng et al [5] showed that, due to the high enthalpy carried by the pyrolysis gas, the gas flow behavior within a charring ablator is crucial to the inner thermal response of the material. In addition, since the gas is eventually blown into the chemical reacting boundary layer [6], correct modeling of the pyrolysis gas is also important to help determine the surface boundary conditions.…”
mentioning
confidence: 99%
“…Recently, Weng and Martin [4] and Weng et al [5] showed that, due to the high enthalpy carried by the pyrolysis gas, the gas flow behavior within a charring ablator is crucial to the inner thermal response of the material. In addition, since the gas is eventually blown into the chemical reacting boundary layer [6], correct modeling of the pyrolysis gas is also important to help determine the surface boundary conditions.…”
mentioning
confidence: 99%
“…The methodology developed and presented here could be use to obtain accurate values of the effective conductivity of realistic three-dimensional material geometry, such as the ones obtained from computed X-ray microtomography [20]. These values could then be used in volume-averaged material response code [31,32] to increase the fidelity in heat transfer analysis.Moreover, performing such an analysis on a real material would allow to compare to experimental analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Table 4 gives the critical velocity result for each Ma. 4 , CO, CO 2 and C 2 H 2 for Ma=8, 9 and 10. It is visible that with an increasing Ma, the types of combustion components increase, the consumption rate of H 2 increases, the production amounts of CH 3 increases at first then decreases, the production amount of CH 4 decreases, the production amount of CO has little difference and the production amounts of H, CO 2 , C 2 H 2 and H 2 O increase.…”
Section: Analysis Of the Critical Velocity Of Pyrolysis Gases At The mentioning
confidence: 99%
“…The pyrolysis of charring ablation materials and the flow of pyrolysis gases in the material can bring off amounts of heat [4][5][6][7]. Meanwhile, the char on the material surface usually ablates because it reacts with the oxygen in the boundary layer behind the shock wave.…”
Section: Introductionmentioning
confidence: 99%